2018
DOI: 10.1371/journal.ppat.1006834
|View full text |Cite
|
Sign up to set email alerts
|

A role for domain I of the hepatitis C virus NS5A protein in virus assembly

Abstract: The NS5A protein of hepatitis C virus (HCV) plays roles in both virus genome replication and assembly. NS5A comprises three domains, of these domain I is believed to be involved exclusively in genome replication. In contrast, domains II and III are required for the production of infectious virus particles and are largely dispensable for genome replication. Domain I is highly conserved between HCV and related hepaciviruses, and is highly structured, exhibiting different dimeric conformations. To investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 82 publications
6
52
0
Order By: Relevance
“…As shown in Fig 7, there was a noticeable increase in the amount of pS225 reactivity between 24-72 h.p.e. As observed previously (19), over time the size of LDs increased and NS5A became almost exclusively associated with the periphery of these LDs. The distribution of pS225 also associated with the periphery of LDs but was restricted to part of the LDs.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…As shown in Fig 7, there was a noticeable increase in the amount of pS225 reactivity between 24-72 h.p.e. As observed previously (19), over time the size of LDs increased and NS5A became almost exclusively associated with the periphery of these LDs. The distribution of pS225 also associated with the periphery of LDs but was restricted to part of the LDs.…”
Section: Resultssupporting
confidence: 86%
“…This is likely due to an effect on genome replication and is consistent with the 10-fold reduction in replication seen previously with the S225A phosphoablatant mutant (37). We also observed that inhibition of these kinases resulted in a loss of co-localisation of NS5A with LDs, suggesting that this association is required for efficient genome replication, in addition to its requirement for virus assembly (19, 47).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations